Pengaruh Media Sosial Terhadap Rendahnya Literasi Akademik Mahasiswa S1 Pada Program Studi Manajemen Universitas Buana Perjuangan Karawang - Falahhuddin, Afif; Puspasari, Ayu Diana; Fasha, Denanda Alivia; Widia, Elta; Hidayah, Fathimah Nur; Harahap, Nabila Susanti; Suteja, Shintia Noviyanti; Susanti, Susanti; Rahayu, Putri Dwi; Wanta, Wanta (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research aims to analyze the influence of social media on the low academic literacy of undergraduate students in the Management Study Program, Buana Perjuangan University, Karawang. This research uses a qualitative method with a case study approach. Data was collected through questionnaires with 35 Management Study Program student respondents, as well as participatory observation in the campus environment. Data analysis was carried out using thematic analysis techniques to identify the main patterns and themes that emerged from the data. The research results show that social media has a complex impact on students' academic literacy. Some students admit that social media often distracts them from academic activities and reduces the time spent reading and writing in depth. In addition, the type of content often consumed on social media, which tends to be more entertainment than educational. However, there are also students who use social media as a source of academic information and discussion, although the number is relatively small.